MENINGKATKAN KESADARAN MASYARAKAT DALAM MENGHINDARI RIBA DI DESA CIBUNIAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Geopani Abad; Rully Trihantana; Ria Kusumaningrum (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract Nowadays, there are lots of people and housewives doing both debt and sale and purchase transactions without regard to usury. This was experienced by residents of West RW 03 Bogor, especially housewives in the transaction. Through community service, student of Institute Agama Islam Sahi Bogor (INAIS) made observations, interviews and socialization regarding usury and bank interest as well as solutions to avoid usury in the People’s Cibuninian, Pamijahan, Kabupaten Bogor. Indonesian people need to know the Islamic banking system where usury can be avoided there. The purpose of this community service was trying to educate the community especially people in the religious community such as People’s RW 03 Cibunian so that they can avoid usury, with a direct material exposure approach to the public. Hopefully, they could understand about usury on conventional bank interest and switch to the Islamic prescribed system. Results of this community service indicated that people in the People’s cibunian became more aware of usury and its types, and began to switch from the conventional financial system which is vulnerable to usury to the Islamic financial system, through opening an account at an Islamic bank as one of one solution to avoid usury. Keywords: Public Awareness, Riba, Sharia Banking Socialization